Efektivitas Relaksasi Otot Progresif Terhadap Tingkat Nyeri Punggung Bawah Pada Ibu Hamil Trimester III Di Wilayah Puskesmas Kagok - Yuni Astuti; Tuti Anggarawati; Alifiah Zahra Nurcahyani; Shella Nur Jayanti (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2023)
The third trimester of pregnancy is the gestational age from 29 weeks to about 40 weeks and ends with the baby being born. Pregnant women entering the third trimester of pregnancy will experience lower back pain due to enlarged uterus and changes in the center of gravity causing discomfort in daily activities. One of the treatments to help reduce low back pain in third trimester pregnant women is progressive muscle relaxation. This type of research is quantitative research using quasy experimental with a one groups pre test-post test design approach and sampling using purposive sampling technique. The research location at the Kagok Health Center with 19 respondents. The instrument used to assess dysmenorrhea pain is the Numeric Rating Scale (NRS). The research data were analyzed using a statistical test, namely the Wilcoxon test. The results of this study indicate that there is an effect of giving progressive muscle relaxation measures to the level of dysmenorrhea pain with a p value of 0.00 (<0.05).